Resilience of health workers in improving the quality of digital-based services: an Islamic community development perspective - Sudirahayu, Ika; Ghozali, Bahri; Tadjuddin, Nilawati; Sonhaji, Sonhaji (Universitas Islam Negeri Raden Intan Lampung, 2024)
: The government is currently encouraging the use of digital technology to improve the quality of health services as a whole. Digital technology has the potential to optimize public health services by increasing efficiency, accessibility, and quality of service. However, along the way, digital-based health services are not easy to implement, there are changes in the work culture of the organization and resistance from users. In this case, resilience is needed, namely the ability of individuals to adapt to environmental changes, survive pressure and challenges, or the ability to overcome difficulties faced, especially in the face of continuous change in the context of a digital health service system. The resilience of health workers not only includes technical aspects, but also ethical values that are in accordance with Islamic teachings. From the perspective of developing an Islamic society, the quality of service must be in line with Islamic ethical and moral values. The purpose of this study is to describe how resilience impacts on improving the quality of digital-based services with a special emphasis on the Islamic community development approach. This study uses a descriptive qualitative method. Data were collected through in-depth interviews with health workers who provide digital-based services, and patients who receive services in outpatient installations, as well as observation and documentation. The results of the study indicate that the resilience of health workers can make a positive contribution to the quality of digital-based health services. The digitalization program can be optimized by implementing the stages of Islamic community development. The community is greatly helped to obtain health services. The novelty of this article lies in the combination of the concept of health worker resilience with the Islamic community development approach in improving the quality of digital-based health services.